A homogeneous group decision making for selection of robotic systems using extended TOPSIS under subjective and objective factors - Bairagi, Bipradas (Decision Making: Applications in Management and Engineering, 2022)
Selection of the best robotic system considering subjective and objective factors is very imperative decision making procedure. This paper presents an extended TOPSIS based homogeneous group decision making algorithm for the selection of the best industrial robotic systems under fuzzy multiple criteria decision making (FMCDM) analysis. FPIS, FNIS, positive and negative separation measures, subjective factor measure, and objective factor measure and robot selection index are computed. A case study has been conducted and illustrated for better clarification and verification of proposed algorithm.